Managing Restaurant’s Food Loss and Waste at The Aburi Sushi Bali: A Sustainable Culinary Tourism Enterprise Model in Bali - I Nengah Subadra (Pusat Kajian Bali Universitas Udayana, 2024)
Food loss and waste (FLW) is a global issue that affects the environment, economy, and society. It also poses a challenge for the sustainability of Japanese culinary tourism which is a growing sector in Bali. This study aims to explore how a sushi restaurant in Bali especially at The Aburi Sushi Bali manages its FLW and contributes to sustainable culinary tourism. The study adopts a qualitative case study approach, using semi-structured interviews, observation, and document analysis as data collection methods. The findings reveal that The Aburi Sushi implements various strategies to prevent, reduce, and recover FLW, such as inventory management, portion control, menu design, staff training, customer education, and food donation. The study also identifies the benefits and challenges of FLW management for the restaurant and its stakeholders. The study concludes that FLW management enhances the environmental, economic, and social sustainability of culinary tourism enterprises in Bali. It also provides implications and recommendations for practitioners and policymakers to improve FLW management practices in the culinary tourism sector